Investigation of Changes of Antioxidant Properties of Coffee through Fermentation by Using Saccharomyces Cerevisiae and Bacillus Subtilis - Dinh, Yen Nhi; Nguyen, Quang Duy; Le, Hong Phu (Journal of Technical Education Science, 2022)
The study was carried out to investigate the changes of antioxidant properties and quality of green coffee beans fermented by using Bacillus subtilis and Saccharomyces cerevisiae as starter cultures in sugarcane and banana juice at different times fermentation. The fermentations were conducted with different juice concentrations for different fermentation times 24, 48, and 72 hours at room temperature. Antioxidant properties were determined by Folin-Ciocalteu reagent for the determination of total phenolic content, DPPH assay for the determination of antioxidant capacity, and colorimetric method used for determination of total flavonoid content. As a result, coffee fermentation at 10oBrix, 107 cells/mL for each type of microbe, and the time (48 hours) had a positive effect on antioxidant properties. However, there was not a significant difference in terms of antioxidant properties between fermented and original coffee beans at optimal conditions. Therefore, antioxidant properties were dramatically reduced during the early stages of fermentation, but it was shown to be able to overcome it through this study. This study is a premise to applying microbial products through fermentation to create a coffee with high antioxidant activity compared to conventional coffee products.